A Simple Method of Improving Microbial Fuel‐Cell Performance Based on Polyaniline/Carbon Composite Anodes. (28th July 2015) - Yuan, Yong; Kim, Sunghyun
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10425-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>